Target Keuangan, Kondisi Industri, Perubahan Auditor, Dan Perubahan Direksi Terhadap Salah Saji Material Pada Laporan Keuangan - Ari Purwanti (Politeknik Ganesha Medan, 2022)
This study aims to investigate how financial targets, industry conditions, changes in auditors and changes in the Board of Directors can affect the occurrence of misstatements in financial statements. By using a research sample of 16 state-owned companies other than banks in 2015 to 2019, this study tested empirically using a multiple regression model. The test results prove that financial targets and changes in the auditor have a significant positive effect on material misstatements in financial statements, but industry conditions have a significant negative effect on material misstatements in financial statements. Meanwhile, changes in directors have no significant effect on material misstatements in the financial statements. These results have implications for the practice of determining the materiality number against the background of the tendency of changes in the pattern of material misstatements in the financial statements under certain conditions.